Efeito fotoprotetor, genoprotetor e antineoplásico da apitoxina da apis mellifera do semiárido brasileiro. - Viana, Geysa Almeida (2019)
This study aimed to evaluate the photoprotective activity in vivo, and the in vitro genoprotective and antineoplastic potential of apitoxin produced by Apis mellifera in the semiarid of Rio Grande do Norte. For this, the antioxidant activities of the aqueous solution of apitoxin were evaluated by the DPPH method (2,2-diphenyl-1-picrilhydrazyl), as well as the in vitro evaluation of its genotoxic and antigenotoxic potential through the comet assay. In vitro antineoplastic activity in human tumor cell lines: poststrate adenocarcinoma (PC3), hepatocellular carcinoma (HEPGE2), melanoma (MAD-MB435) and astrocytoma (SNB19) were verified by the MTT [3- (4 bromide) colorimetric method-5-dimethylthiazol-2-yl) -2,5- diphenyltetrazolium], as well as cytotoxic activity in normal fibroblast (L929) and keratinocyte (HACAT) cells. The in vivo photoprotective effect of apitoxin gel was evaluated in 16 Wistar rats and was divided into four experimental groups with 4 rats in each: Group 1 (G1) composed of rats in which the skin of the dorsal region did not receive topical gel application apitoxin base and was not subjected to UVB irradiation; Group 2 (G2) whose animals' skin was not subjected to topical gel application and were irradiated; Group 3 (G3) whose skin was subjected to topical application of 2.5% apitoxin-based gel and irradiated and Group 4 (G4), where the skin was subjected to topical application of apitoxin-based gel to 5.0% and subjected to irradiation. In antioxidant activity, the results show that the inhibitory capacity of apitoxin solution (IC50) was 0.648 mg / mL. The highest percentages of DPPH inhibition were obtained at concentrations of 1mg / mL and 0.8mg / mL, which were respectively 74.92% and 60.85%. Apitoxin had no genotoxic effect on L929 cells at concentrations of 30 μg / mL, 10 μg / mL and 5 μg / mL after 24 hours of exposure. This effect was only evidenced at 50 μg / mL. Also, at all concentrations tested, apitoxin promoted a significant reduction in DNA damage index (idDNA) when compared to the positive control (cells treated with H2O2). The antineoplastic potential was demonstrated in vitro, since at concentrations of 50 μg / mL and 25 μg / mL cytotoxic effect was observed, with significant reduction of viability percentages of PC3, HEPGE2, MAD-MB435 and SNB19 tumors, but not presented cytotoxicity in normal L929 and HACAT cells, suggesting a selective action. It was evidenced that the apitoxin-based gel was able to protect the skin from UVB irradiation, since the skin of G3 and G4 animals showed similar macroscopic and histological morphological pattern to G1, whereas in the skin of G2 rats were observed on macroscopic examination focal areas of burn and erythema, and on histological examination keratinocyte necrosis, presence of inflammatory cells, mast cells, vascular congestion, interstitial edema and collagen fiber dissociation. The high antioxidant activity evidenced, associated with the absence of genotoxic, genoprotective and cytotoxic effects in normal cells, provide evidence of the therapeutic potential of apitoxin, and confirm its antineoplastic effect on PC3, HEPGE2, MAD-MB435 and SNB19 tumor lines, its use in photoprotective cosmetic formulations.